Presence of Potyvirus in the Norte de Santander department and molecular characterization of NIb protein in Colombian SCMV isolates (2021)
Potyviruses are the largest genus of plant viruses that cause significant losses over a wide range of crops. In this paper, the presence of potyvirus in different plant crops in the provinces of Ocaña and Pamplona located in the north and south of the Department of Norte de Santander (Colombia) was evaluated with RT-PCR analysis using universal oligonucleotides specific to the region that encodes the NIB protein. The results indicate the presence of several potyvirus in Pamplona in economically important crops such as corn (Zea mays), tomato (Solanum lycopersicum), potato (Solanum tuberosum) and zucchini (Cucurbita pepo). In Ocaña, potyvirus was found in bean (Phaseolus vulgaris), corn and pumpkin (Cucurbita maxima/i>). In corn, one of the most important crops, the presence of the Sugarcane mosaic virus (SCMV) was confirmed with nucleotide sequencing. This is the first report of this virus in the department. The presence of several potyviruses in different crops in Norte de Santander indicate an alarming phytosanitary condition that must be addressed with priority to establish detection and control systems that maximize production, ensure agricultural sustainability, and propose certification schemes and improvement programs to reduce economic losses.